2019
DOI: 10.17094/ataunivbd.588666
|View full text |Cite
|
Sign up to set email alerts
|

Gebe Konya Merinosu Koyunlarında Erken Gebelikte Gebelik İlişkili Glikoproteinlerin Plazma Profilinin Belirlenmesi

Abstract: Öz: Bu çalışmada, sığır ELISA-PAG (gebelik ilişkili glikoprotein) kitinin Konya Merinosu koyunlarda; 1) gebeliğin teşhisi ve 2) PAG'lerin erken gebelik plazma profilinin belirlenmesindeki kullanılabilirliği değerlendirildi. Bu amaçlar için, kan örnekleri gebeliğin 21-70. günleri arasında haftalık olarak alındı. Kit üreticisinin talimatına göre, PAG'lerin plazma seviyeleri belirlendi ve değer 0.3 OD'nin (optimal yoğunluk) üzerinde ise gebelik tanısı pozitif olarak kabul edildi. Gebeliğin 21 ve 70. günleri arası… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…Furthermore, sensitivities similar to the sensitivity determined for the rapid visual PAG ELISA in the present study were reported for the "Idexx visual pregnancy test" in Santa Ines ewes 30 days after laparoscopic insemination (Chaves et al, 2017) and for the "Idexx bovine pregnancy test" in Corriedela and Ile de France x Texel sheep throughout pregnancy (Rovani et al, 2016). On the other hand, Kaplan et al (2019) reported a low sensitivity for the "Idexx bovine pregnancy test" before the 56th day of pregnancy in Konya Merino sheep. In addition, Chaves et al (2017) determined a lower sensitivity for the "Idexx visual pregnancy test" on day 26 post-mating compared to day 28 post-mating (73.17 versus 92.68, respectively).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, sensitivities similar to the sensitivity determined for the rapid visual PAG ELISA in the present study were reported for the "Idexx visual pregnancy test" in Santa Ines ewes 30 days after laparoscopic insemination (Chaves et al, 2017) and for the "Idexx bovine pregnancy test" in Corriedela and Ile de France x Texel sheep throughout pregnancy (Rovani et al, 2016). On the other hand, Kaplan et al (2019) reported a low sensitivity for the "Idexx bovine pregnancy test" before the 56th day of pregnancy in Konya Merino sheep. In addition, Chaves et al (2017) determined a lower sensitivity for the "Idexx visual pregnancy test" on day 26 post-mating compared to day 28 post-mating (73.17 versus 92.68, respectively).…”
Section: Resultssupporting
confidence: 84%
“…PAG ELISA pregnancy tests commercially validated for cattle have been used in various Brasilian and European sheep breeds (Rovani et al, 2016;Chaves et al, 2017;Steckeler et al, 2018). It is stated that PAG profiles in the peripheral blood can vary between sheep breeds; therefore, determining the specific PAG profile of breeds native to Turkey is important for improved reproductive management (Kaplan et al, 2019). The aim of this study was to evaluate the diagnostic reliability of a bovine rapid visual PAG ELISA test and transabdominal ultrasonography in standing position for early pregnancy diagnosis in Awassi sheep using lambing results as a gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…PAGs are specific proteins that aid in pregnancy diagnosis and small ruminant management. However, different results have been reported for PAGs levels, which show volatility during the early gestation period (El Amiri et al, 2014Kaplan et al, 2018;Ranilla et al, 1994). Previous studies also suggest that differences in PAGs or PSPB levels could be associated with the sheep breed (Redden & Passavant, 2013;Ranilla et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Serum Kaplan et al, 2018;Ranilla et al, 1994) for results pertaining to early gestation are attributed to the genetic variations of breeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the progression of implantation and placentation, they reach a much higher concentration than can be detected in maternal circulation on day 35. Moreover, the PAGs level in the maternal blood reaches the highest level at the end of the pregnancy due to the increase in the functional mass of the placenta [9,10,11]. It is stated that the migration of binuclear trophoblastic cells to maternal tissue and their association with endometrial cells further facilitate the detection and passage of PAGs into the maternal circulation [3].…”
Section: Introducti̇onmentioning
confidence: 99%